PELAKSANAAN PERJANJIAN SEWA MENYEWA KOS VERLINA SECARA LISAN BERDASARKAN ASAS ITIKAD BAIK DI KOTA PEKANBARU - Wulandari, Intan; Firdaus, Firdaus; Hendra, Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Agreements are an inseparable part of human life, starting from those made inwriting or unwritten. In principle, a rental agreement is a form of economic relationshipbetween the owner of the premises (the renter) and the tenant of the premises. Good faith isone of the principles of agreements, which is contained in Article 1338 paragraph (3) of theCivil Code, namely that agreements must be implemented in good faith. The implementationof the principle of good faith in the rental agreement for the Verlina boarding house inPekanbaru City is analyzed from the pre-contractual, contractual and post-contractualstages. This research aims to find out how the Verlina Boarding House room rentalagreement is implemented verbally based on the principle of good faith and the efforts thatmust be made so that the parties are obedient and obedient in implementing the VerlinaBoarding House room rental agreement verbally based on the principle of good faith inPekanbaru City.The type of research used is sociological legal research, namely legal research thatanalyzes the application of law in a real sense in society based on facts that exist in a society.The population and sample are all parties related to the problem being studied. This researchuses data sources in the form of primary data and secondary data, and data collectiontechniques are carried out using interviews and questionnaires.The results of this research are the implementation of the Verlina boarding house roomrental agreement orally based on the principle of good faith in Pekanbaru City between theboarding house owner and the boarding house tenant at the pre-agreement and contractualstages, the principle of good faith has been fulfilled, but at the post contractual there is adefault that occurs, the boarding house renter does not apply objective good faith inimplementing the agreement, especially in carrying out the boarding house renter'sobligations towards the boarding house owner, namely there are tenants who are late infulfilling their achievements in the form of not being on time in making payments for theboarding house rent. and being negligent in carrying out achievements by violating the rulesand regulations in the boarding house, there are boarding house tenants who are dishonestand run away before paying the boarding fee, causing losses to the boarding house owner.Efforts that must be made to ensure that the parties comply with the implementation of theagreement are to be given strict sanctions in the form of warnings and fines if they do not payboarding fees on time and fines for violations of regulations in the boarding house and toenforce the existence of guarantees in the boarding house rental agreement.Keywords: Verbal Agreement, Lease, Boarding House, Principle of Good Faith.